Molecular identifications of land snails (Gastropoda) and determination of its associated parasites (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Freshwater snail is known to be an intermediate host for parasites. However, little is known on terrestrial snails whether they can become host for any parasites as well. The identification of the land snails also need confirmation as there are disagreements on the classification result of land snail species. Therefore, this study was conducted to determine the prevalence of snail parasites in livestock and poultry farms from Penang and Kedah, Malaysia. Identification of the snail species was conducted based on the morphological features and mitochondrial cytochrome c oxidase subunit I (COI) gene analysis. Out of 105 individual snails collected, four species were found in this study with the highest prevalence of 47.62% (50/105) snails identified as Physella acuta followed by Macrochlamys sp. with 31.4% (33/105). While 14.3% (15/105) were identified as Physella cubensis and the lowest prevalence was identified as Filopaludina sp. with 6.7% (7/105). Among these four species, only Physella acuta and Macrochlamys sp. were found to be infected with helminth parasites namely trematode and nematode. Macrochlamys sp. recorded the highest prevalence of parasitic infection with the prevalence of 87.9%. Besides, there are 134 of endoparasite and 36 of ectoparasite found in this study namely, Barchylaima fuscatum (helminth), 3 unknown nematode, and 36 Riccardoella limacum or slug mite which was found on the surface and in the mantle cavity of the snails.
Keywords: Gastropoda; Mitochondrial COI gene; Parasitic infection; Shell characteristics